The availability and accessibility of urban green space in Kuala Lumpur City Centre - Mohammed, Yakubu (2017)
Urban green space plays a vital role in recreation, health and supporting everyday life. Accessibility is one of the important factors that influences the use of green space thereby increasing the quality of life and well-being of city residents. The problem of this research work was that, it was investigated that some available green space in the study area were not easily accessible by the users due to numbers of factors which necessitate the need and purpose of this study. Hence the aim of this study is to identify the availability of urban green space and to provide useful information that will improve its accessibility. Spatial data were used to identify the availability of urban green space and the views of expert in built environment about factors of urban green space accessibility were obtained with the aid of a questionnaire. The major findings of this research work was that the available green space is adequate as the result show that about 1.7 Ha per 1000 based on WHO standard. Three factors of urban green space accessibility are identified which include location, quality and quantity factors, but this study suggests to focus on two (Location and quality). Based on spatial analysis, nine sites are highly accessible, four are moderately accessible and three are less accessible. This study recommended that city authority and green space managers should apply the most important factors which are location and quality factors of urban green space accessibility in future design as this will go along way to improve accessibility.